PENERAPAN MODEL COOPERATIVE LEARNING UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA DI SEKOLAH DASAR - I Gusti Ayu Putu Lila Engelina; Ni Kadek Noviyanti; Ni Kadek Mia Adeliani; Kadek Mas Aishwarya Ari Canti; I Made Sujana Adnyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' numeracy skills in solving mathematical story problems through the implementation of the Cooperative Learning model in elementary schools. This study used a Classroom Action Research (CAR) approach, implemented in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 25 third-grade elementary school students. Data were collected through numeracy tests, observation sheets, and documentation of learning activities. The results showed that the implementation of the Cooperative Learning model significantly improved students' numeracy skills. This improvement was evident in the increase in average numeracy test scores from cycle I to cycle II, as well as an increase in the percentage of learning completion. Furthermore, student engagement in the learning process also showed positive developments. Students became more active in group discussions, helped each other understand story problems, and were more confident in expressing their opinions and solutions. The Cooperative Learning model provides opportunities for students to learn collaboratively, enabling them to rely not only on individual abilities but also on the strengths of teamwork. This makes the learning process more meaningful, as students can connect mathematical concepts to real-world experiences through social interaction. Thus, the application of the Cooperative Learning model has proven effective in improving students' numeracy skills as well